(untitled) (UUM Journal of Legal Studies, 2025)
Smart cities are the future of urban development as they incorporate state of the art technology to enhance the living standards of the citizens. However, these advances have real challenges in terms of data protection, more so in countries like Malaysia, where the legal aspects are still developing. This paper will critically analyze Malaysia’s legal framework for data protection in the context of the Malaysian Smart City Framework and its data collection and processing practices. In this paper, the three fundamental principles of data protection, namely necessity, consent and safeguards will be examined. Using a comparative law approach, this research compares Malaysian laws with international standards, in particular the General Data Protection Regulation of the EU. This comparison shows some serious gaps and hurdles in Malaysia’s approach, particularly with regard to protection from automated decision-making and surveillance technology. This research will also show that Malaysia must improve its legislation to ensure privacy will not be invaded when the smart city technologies are have already become so widespread. The findings advocate the need for Malaysian laws and policies to be positively realigned with technology to create a privacy-aware model and fit for purpose for the shifting requirements of smart urban arenas.